1977
DOI: 10.1126/science.404709
|View full text |Cite
|
Sign up to set email alerts
|

GM 2 Ganglioside Lysosomal Storage Disease in Cats with α-Hexosaminidase Deficiency

Abstract: Two kitteens with progressive neurologic disease had increased concentrations of GM2 ganglioside in their cerebral cortex. Examination under the light microscope revealed cytoplasmic vacuolation of neurons and hepatocytes. Transmission and scanning electron microscopy demosntrated cytoplasmic inclusions encompassed by membranes in various central nervous system cell types and in hepatocytes. Beta-D-N-acetyl-hexosaminidase activity was reduced to about 1.0 percent of normal in brain, liver, and cultured skin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
2

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(64 citation statements)
references
References 8 publications
0
62
2
Order By: Relevance
“…In contrast to a previous study, which showed that GM2 was about 42% of the total brain ganglioside distribution in the SD cat, we show that GM2 accounts for 67% of the total ganglioside distribution in the SD cat (19). The ganglioside distribution in the SD cat in the previous study was analyzed at an earlier age (11 weeks), which could account for the lower GM2 distribution (19). For our study, we analyzed the total brain ganglioside distribution at a similar time-point in disease progression in the SD mouse, cat, and human, and we showed that GM2 accumulation in the SD cat is intermediate between the SD mouse and the SD patient.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In contrast to a previous study, which showed that GM2 was about 42% of the total brain ganglioside distribution in the SD cat, we show that GM2 accounts for 67% of the total ganglioside distribution in the SD cat (19). The ganglioside distribution in the SD cat in the previous study was analyzed at an earlier age (11 weeks), which could account for the lower GM2 distribution (19). For our study, we analyzed the total brain ganglioside distribution at a similar time-point in disease progression in the SD mouse, cat, and human, and we showed that GM2 accumulation in the SD cat is intermediate between the SD mouse and the SD patient.…”
Section: Discussioncontrasting
confidence: 53%
“…The SD cats were obtained from the fG M2 Baker colony and have been previously described (17,19). Sequence analysis determined that the causative mutation in this domestic shorthair SD cat resulted from a 25-base-pair inversion at the 3' end of the Hexb gene (16).…”
Section: Catsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, deleterious mutations in the HEXB gene encoding the b-subunit of Hex molecules affect both Hex A and Hex B, producing the null (0) variant of GM2 gangliosidosis (human Sandhoff disease) and lysosomal storage of undegraded GM2 ganglioside in neurons as a major storage material. 5 In domestic animals, naturally occurring Sandhoff-like disease has been reported in only 2 canine breeds (i.e., a Golden Retriever 18 and toy Poodles 16 ) and 4 feline breeds or families (i.e., domestic cats in the United States, 4 Korat cats, 13 Japanese domestic cats, 19 and European Burmese cats 3 ). At present, the pathogenic mutations in all 4 feline families have been identified, 3,8,11,12 but not in canine breeds.…”
mentioning
confidence: 99%